THE PROBLEM OF QUANTITY AND QUALITY IN HIGHER EDUCATION IN THE CONTEXT OF THE UNIVERSITY NETWORK IN UKRAINE - Ogneviuk, Victor; Lugovyi, Volodymyr (Educological discourse, 2022)
Improving the competitiveness of higher educational institutions in Ukraine is an urgent problem due to the strengthening of social responsibility of education, society’s demand for quality, innovative, leadership-based higher education, integrated into the European educational space, as well as due to the devastating effects of the war and demographic problems. Within the framework of "University Studies" as a sub-direction of "Educology", the condition of the network of the state higher educational institutions, their compliance with modern and post-war needs of Ukraine’s reconstruction, increasing the competitiveness of domestic universities, have been analyzed. It has been found out that the economy and the country’s state budget are not able to ensure the effective operation of the existing network of the state higher educational institutions due to its scatterization and fragmentation, duplication of training, resource and infrastructural weakness. At the same time, the existing network of state higher educational institutions is not able to fully meet the needs of citizens, society and economy. Therefore, optimization of the university network is needed. There is a need for consistent state policy and a system of appropriate measures to optimize the network of the state higher educational institutions in the regions. The article substantiates the Concept of ensuring the competitiveness of higher educational institutions of Ukraine, which provides for pooling of human, financial, material resources of higher educational institutions suffering from the demographic crisis, destruction of infrastructure during the war with RF, lack of finance to transform higher educational institutions into powerful competitive regional institutions.